ASUPAN ZAT GIZI MAKRO DAN SERAT SERTA STATUS GIZI PADA SISWA MADRASAH ALIYAH NEGERI 1 MEDAN TAHUN 2016 - Qonita Luthfia; Etti Sudaryati; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Nutritional problem is the problem of an unbalanced food intake. Nationally, the obese prevalence of adolescents in Indonesia amounted to 10.8%, consisting of 7.3% fat, 3.5% are very overweight (obese) and the prevalence of underweight 11.1% consisting of a very thin 3.3% and 7.8% thin. Riskesdas data changes from 2010 to 2013 to the prevalence of obese adolescents are in 2010obese adolescents of 1.4% and in 2013 obese adolescents 7.3% . These data show that each year more and more teenagers are not balanced in regulating the diet. The purpose of this study was to determine the intake of macro-nutrients and fiber also the nutritional status of MAN 1 in 2016. This research included descriptive study conducted in Madrasah Aliyah Negeri 1 Medan, the results showed the samples taken amounted to 100 students by using stratified random sampling.Analisis data using frequency distributions and cross-tabulations. The results of this study indicate the nutritional status according to IMT / U on the students of Madrasah Aliyah Negeri 1 Medan the most category of fat 46%, and the least thin 20%, then the normal nutritional status, namely 34%, whereas there is no nutritional status of very thin and obesity. Energy intake is less than the limit of AKG is 44% , carbohydrate intake is less than AKG limit is 47%, protein intake is more than the AKG limit is 52%, fat intake is more than the AKG limit is 45% and fiber intake is less than the AKG limit  is 73% Required counseling for students about a balanced intake of nutrients so that the nutritional status of students is in the normal category. One of the efforts undertaken by schools is the provision of a healthy canteen. Keywords :the intake of macro nutrients, fibers, Nutritional Status